Electroacupuncture promotes motor function and functional connectivity in rats with ischemic stroke: an animal resting-state functional magnetic resonance imaging study. Issue 2 (April 2021) - Li, Zuanfang; Yang, Minguang; Lin, Yunjiao; Liang, Shengxiang; Liu, Weilin; Chen, Bin; Huang, Sheng; Li, Jianhong; Tao, Jing; Chen, Lidian
Background: To evaluate whether electroacupuncture (EA) treatment at LI11 and ST36 could reduce motor impairments and enhance brain functional recovery in a rat model of ischemic stroke. Methods: A rat model of middle cerebral artery occlusion (MCAO) was established. EA at LI11 and ST36 was started at 24 h (MCAO + EA group) after ischemic stroke modeling. Untreated model (MCAO) and sham-operated (Sham) groups were included as controls. The neurological deficits of all groups were assessed using modified neurologic severity scores (mNSS) at 24 h and 14 days after MCAO. To further investigate the effect of EA on infarct volume and brain function, functional magnetic resonance imaging was used to estimate the size of the brain lesions and neural activities of each group at 14 days after ischemic stroke. Results: EA treatment of MCAO rats led to a significant reduction in the infarct volumes accompanied by functional recovery, reflected in improved mNSS outcomes and motor functional performances. Furthermore, functional connectivity between the left motor cortex and left cerebellum posterior lobe, right motor cortex, left striatum and bilateral sensory cortex were decreased in MCAO group but increased after EA treatment. Conclusion: EA at LI11 and ST36 could enhance the functional connectivity between the left motor cortex and the motor function-related brain regions, including the motor cortex, sensory cortex and striatum, in rats. EA exhibits potential as a treatment for ischemic stroke.